Siegel's robust regression model in analyzing the effect of organizational interest on student academic achievement - Rahma Faelasofi; Cahyadi, Rahman; Sabila, Amy; Hendrowati, Tri Yuni; M. Badrun (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to understand how students’ interest in participating in campus organizations relates to their academic performance. The question is not simply whether interest leads to better grades, but how this interest, which grows from personal motives and external influences, might interact with students’ learning habits in ways that are not always linear or predictable. Method: The research involved 140 students, and organizational interest was measured using a questionnaire that had been validated through confirmatory factor analysis. GPA was collected as the measure of achievement. When the data were examined, both variables showed clear deviations from normality and contained several outliers. Rather than forcing the data into a conventional regression model, the study employed Siegel’s median-based robust regression, which is more capable of producing stable estimates when extreme values distort the usual assumptions. Findings: The analysis showed that organizational interest is supported by indicators with adequate loading values, and the regression results revealed a positive and statistically meaningful relationship between interest and GPA. Students who expressed stronger organizational interest tended to earn higher academic scores, even when the data’s irregularities were taken into account. Significance: The study suggests that organizational engagement is not merely an extracurricular activity but a space where students develop habits and skills that support academic success. It also underlines the value of choosing analytical methods that genuinely fit the nature of educational data, especially when they contain outliers or non-normal patterns.